Preliminary observations on the mandibles of palaemonoid shrimp (Crustacea: Decapoda: Caridea: Palaemonoidea). - Ashelby, C; De Grave, S; Johnson, M (PeerJ, 2015)
The mandibles of caridean shrimps have been widely studied in the taxonomy and functional biology of the group. Within the Palaemonoidea the mandibles reach a high level of structural diversity reflecting the diverse lifestyles within the superfamily. However, the majority of studies have been restricted to light microscopy, with the ultrastructure at finer levels poorly known. This study investigates the mandible of nine species belonging to six of the recognised families of the Palaemonoidea using SEM and analyses the results in a phylogenetic and dietary framework. The results of the study indicate that little phylogenetic information is conveyed by the structure of the mandible, but that its form is influenced by primary food sources of each species. With the exception of Anchistioides antiguensis, all species examined possessed cuticular structures at the distal end of the pars molaris (molar process). Five types of cuticular structures are recognised herein, each with a unique form, but variable in number, placement and arrangement. Each type is presumed to have a different function which is likewise related to diet.